Recall Length and Measurement Error in Agricultural Surveys - Wollburg, Philip; Tiberti, Marco; Zezza, Alberto (World Bank, Washington, DC, 2020)
This paper assesses the relationship between the length of recall and nonrandom error in agricultural survey data. Using data from the World Bank's Living Standards Measurement Study–Integrated Surveys on Agriculture in Malawi and Tanzania, the paper shows that key input and output variables are systematically related to the length of the recall period, indicating the presence of nonrandom measurement error. With longer recall periods, farmers report greater quantities of harvest, labor, and fertilizer inputs. Farmers list fewer plots as the recall period increases. The paper argues that it is plausible that farmers overestimate plot-level outcomes, or they forget some of their more marginal plots due to longer recall periods. The analysis also finds evidence of measurement error related to the length of recall in common measures of agricultural productivity. The size of the recall effect typically varies between 2 and 5 percent per additional month of recall length, which is economically significant. With data reliability affecting policy effectiveness, improving agricultural survey data quality remains an important concern. Mainstreaming objective measures where possible and reducing the risk of recall error through shorter recall periods appear to be promising avenues to improve the quality of key variables in agricultural surveys.